Witchcraft, Subjectivation and Sovereignty: Foucault in Cameroon - Hengehold, Laura (Sens public)

(untitled) (Département des littératures de langue française, 2009)
What does the status of the occult in contemporary African politics have to tell us about the processes of subjectivation and sovereignty described in Foucault’s genealogy of Western biopolitics? Ideas about the invisible that have become strikingly popular in African societies undergoing rapid economic transformation may allow African philosophers and anthropologists to situate European forms of subjectivation, sovereignty, knowledge, and visibility with respect to their own “invisible” or occult dimension. My goal is arrive at a better understanding of what philosophers, Northern or Southern, mean by political imagination and to explain how power involves the capture of an individual’s or community’s imagination as well as their visible, tangible bodies.